Integration of Qur'anic Parenting, Digital Literacy, and Cultural Values in Preventing Online Gambling Addiction in Young Children - Derysmono; Muqoddam Cholil; Syarifuddin; Kieren Akbar; Budi Marta Saudin (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
The increasing prevalence of online gambling addiction among young children demands a preventive strategy that is both spiritually grounded and culturally contextualized. This study proposes the integration of Qur’anic Parenting, Digital Literacy, and local Cultural Values as a comprehensive approach to this issue. Qur’anic Parenting emphasizes moral and spiritual development rooted in Islamic teachings, while Digital Literacy enhances children's ability to engage safely and critically with digital platforms. Crucially, cultural values such as gotong royong—as embodied in the traditional Bugis practice of Maccerak Parek in Tanjung Jabung Timur, Jambi—highlight collective responsibility and mutual assistance within the community. In this tradition, the spirit of cooperation transcends familial boundaries and fosters communal vigilance, making it a valuable social mechanism in monitoring and guiding children's behavior. The synergy of these three domains provides a holistic and culturally embedded model to protect children from the harmful impact of online gambling.